2018
DOI: 10.13005/ojc/340539
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dopant Ions on the Properties of Polyaniline Conducting Polymer

Abstract: This work will show, for the first time, the effect of nicotinic acid (NA) and 2-methylnicotinic acid (MNA)on the synthesis and properties of conducting polyaniline (PANI). The work investigates the effects of sulphuric acid (H2SO4), nicotinic acid (NA), and 2-methylnicotinic acid (MNA) on the synthesis and properties of polyaniline. The results show that the preparation of polyaniline from a sulphuric acid electrolyte is faster than the preparation from nicotinic acid and 2- methylnicotinic acid electrolytes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 49 publications
3
34
0
Order By: Relevance
“…The first reducing peak for Cu was shown at +0.51 V which corresponded to the reduction of Cu 2+ to Cu + , whilst the second reducing peak at -0.33 V and indicated the reduction of Cu + to Cu 0 , in the process of which metallic copper was deposited on the electrode surface. The above was identical to previous work reported in the literature, [51,53,62] where the Abbott group studied the electrolytic deposition of Cu coatings in ionic liquids. They found that Cu species have two stripping and reduction potentials.…”
Section: Cyclic Voltammetry Studiessupporting
confidence: 84%
See 1 more Smart Citation
“…The first reducing peak for Cu was shown at +0.51 V which corresponded to the reduction of Cu 2+ to Cu + , whilst the second reducing peak at -0.33 V and indicated the reduction of Cu + to Cu 0 , in the process of which metallic copper was deposited on the electrode surface. The above was identical to previous work reported in the literature, [51,53,62] where the Abbott group studied the electrolytic deposition of Cu coatings in ionic liquids. They found that Cu species have two stripping and reduction potentials.…”
Section: Cyclic Voltammetry Studiessupporting
confidence: 84%
“…[41,42] DESs can be used in various important industrial fields such as electropolishing, [43,44] electroplating, [19,45,46] metal oxide processing [47] and polymer synthesis. [48][49][50][51] This type of liquid has solved some of the more pressing problems associated with the electrodeposition of metals from aqueous and non-aqueous solutions, and from which the electrodeposition of Zn, [17] Ni, [52] Cu, [53] Cr, [54] Ag, Sn and Co has been achieved. However, relatively little research has actually examined the electrodeposition of metals from DESs, or indeed the effects of additives on the same.…”
Section: Introductionmentioning
confidence: 99%
“…Electroactive polymers such as polypyrrole [13], polyaniline [14], poly (3,4-ethylenedioxythiophene) (PEDOT) [15] and their derivatives have high intrinsic conductivities and have been intensively studied to date [16]. These materials have a key role in electrocatalysis, energy storage, and electrochemical sensors because of their unique properties such as stability, exibility, simple synthetic processes and low cost [17].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is of immense importance to incorporate specific ions of interest into polymer matrix for the control release and selective interaction of dopant anions during corrosion protection of metals, cyclic redox process of supercapacitors, drug delivery, and other analytical applications [4,7]. In this regard, the choice of dopant anion for intercalation in PANI during the polymerization as well as exchange with the counter    MATERIALS INTERNATIONAL | https://materials.international | 55 anion of the electrolyte during electrochemical redox process profoundly matters [3][4]8].…”
Section: Introductionmentioning
confidence: 99%
“…This is anionic doping of polymer which is accomplished by replacement of electrolyte anion resulting in structural modification in the polymer matrix [4,5,16]. On the other hand, introduction of large sized anions into PANI matrix are sterically confined due to which anionic exchange during electrochemical redox process is replaced by rapid proton exchange process [8]. Earlier, we reported the chemical synthesis of PANI and its electrochemical activity in aqueous acidic electrolytes (HClO 4 , H 2 SO 4 , and H 3 PO 4 ) by using Cyclic Voltammetry (CV) [1].…”
Section: Introductionmentioning
confidence: 99%